Factors associated with depression, anxiety, and stress among food industry workers: a systematic review - Zamberi, Mohd Zafrullan; Abdul Razak, Muhammad Izmanuddin Fitri; Sapawi, Amirul Asraf; Hamzah, Khadijahtul Qubra Amizah; Dapari, Rahmat; Che Dom, Nazri; Hassan, Mohd Rohaizat; Syed Abdul Rahim, Syed Sharizman (Malaysian Journal of Public Health (MJPHM), 2023)
In 2021, food industry workers represented approximately one-tenth of the total labour force in Malaysia. There was an estimated 15% of working-age adults who experienced a mental disorder worldwide in 2019. To make the situation worse, service workers in food retail and food services face tremendous stress and mental health consequences during the COVID-19 pandemic. Various study found that worsening mental health and psychological distress have been accelerated substantially by the pandemic. An unsafe or unhealthy working environment can undermine mental health, as poor mental health can interfere with a person’s ability to work if left unsupported. This systematic review aimed to evaluate findings related tofactors associated with depression, anxiety, and stress among food industry workers. Articles related to these factors were collected electronically from two different databases (EBSCOHOST and Scopus). An independent reviewers screened the titles and abstracts of the collected articles from each database, and then stored them in Google Sheet based on the inclusion and exclusion criteria. Next, the included articles were critically appraised to assess the quality of the studies using the Mixed Methods Appraisal Tool (MMAT).Out of the 292 articles identified, four were included in the final review. Sociodemographic characteristics, as well as biological, psychological, and occupational factors were found to be associated with common mental issues among food industry workers. By identifying the risk factors, specific interventions can be implemented by the employers and other relevant parties to prevent, promote, protect, and support the mental health well-being of food industry workers. These findings may be utilised to improve the implementation of key interventions directed to prevent, promote, protect, and support the mental health of food industry workers. Consequently, an enabling environment can be created to address mental health at work, as outlined bythe World Health Organization (WHO). Employers may adapt or revamp their work environment to minimise exposure to psychological risks among their workers, which could prevent workers from experiencing adverse mental health conditions. Workers should also be equipped with awareness and skills, as well as opportunities to recognise and act early on mental health issues in order to promote and protect their mental health. Moreover, workers with pre-existing or ongoing mental health conditions should receive support to access job opportunities, or continue working, and thrive at work,since good mental health status at work can improve an individual’s performance and productivity.